Entomopathogenic fungi (Hypocreales: Ophiocordycipitaceae) infecting bark lice (Psocoptera) in Dominican and Baltic amber. Issue 1 (2nd January 2020) - Poinar, George; Vega, Fernando E.
ABSTRACT: Ophiocordyceps dominicanus Poinar & Vega sp. nov. in Dominican amber and Polycephalomyces baltica Poinar & Vega sp. nov. (Hypocreales: Ophiocordycipitaceae) in Baltic amber are described as entomopathogenic fungi of bark lice (Psocoptera). The specimens possess several features unknown in extant synnematous entomopathogenic fungi such as a tubular dark synnema with a straight, pointed tip bearing spores over the entire surface in O. dominicanus, and a globular yellowish synnema developing on the tip of the host's antenna in P. baltica . These are the only known fossil entomopathogenic fungi of bark lice, making them unique not only for their characters but also in respect to their selection of developmental sites on their bark lice hosts.